Seismic Vulnerability Assessment of Andean Constructions: Structural Typification of Historical Churches Using Digital Technologies. Issue 1 (2nd January 2023) - Aguilar, Rafael; Huaranga, Steffi; Pórcel, Patricia; Zavala, Guillermo
ABSTRACT: This paper describes the implementation of a comprehensive strategy for the structural typification of historical buildings located in earthquake-prone regions using digital technologies such as HBIM and Augmented Reality. The paper starts by presenting a detailed analysis of a selected sample of case studies in Peru in which key structural and architectural features were identified, aiming at proposing a preliminary typological classification. This typification was then optimized by analyzing its application in a larger data set consisting of 311 churches located in the Central Andes region. This allowed formalizing 12 structural typologies, which demonstrated to have the potential to provide an accurate description of the geometrical, material, and structural characteristics of Andean churches. The paper underlines the importance of combining digital technologies and comprehensive engineering analyses for creating tools that will facilitate further structural evaluations and seismic vulnerability assessments at a territorial scale. For the study, these tools improved information management processes, analyses, and post-processing tasks, and facilitated communication and decision-making among stakeholders.